The Urgency of Regulatory Reform in the Treatment of Narcotics Abusers Following Immediate Arrests - Mohamad Adam; Fenty U. Puluhulawa; Dian Ekawaty Ismail (International Journal of Law, Crime and Justice, 2025)
The purpose of the study was to analyze the legal status of narcotics abusers after the hand-holding operation. This type of research is normative legal research with a legislative approach, a case approach and a conceptual approach. The analysis used in this study is qualitative data analysis through the management of legal materials in a deductive way. Based on the research, the results of the research were obtained that in Law Number 35 of 2009 concerning Narcotics, it is stated that after the arrest operation or after the seizure, within a minimum of 3 x 24 hours an evidence test must be carried out to ensure the narcotic content found, then this can have implications for the legal status of a person arrested in the arrest operation. A person caught in a narcotics case can have several possible legal statuses, including; as an arrested witness, if he is only at the scene of the incident without direct evidence of his involvement; as a suspect, if there is preliminary evidence that he possesses or uses narcotics; as a person without legal status who is temporarily detained, if his status is still waiting for the results of laboratory tests of evidence. Therefore, it is necessary to update regulations through the revision of the Narcotics Law which must contain clear time limits on how a person who is caught must be treated before the results of the evidence test come out..